ASESMEN TERHADAP KETERAMPILAN MAHASISWA BIMBINGAN DAN KONSELING DALAM MENYUSUN SKRIPSI PENELITIAN KUALITATIF - Ferdiansyah, Muhammad (JURNAL FOKUS KONSELING, 2016)
Guidance and Counseling majors students of FKIP, University of PGRI Palembangoften use qualitative research design in completing thesis. This study aims to identifiedstudentsâ difficulties in finishing final task based qualitative design. This study useddescriptive case study. In collceting the data, the researcher used interview, observation,and documentataion. Informan was selected using purposive sampling technique. Theresearch finding was tested the trustworthiness by using four criteria : (1) credibilitytest, (2) transferability test, (3) dependability test), (4) Confirmability test. The resultshows that guidance and counseling students got difficulties in determining researchplan, they can not perform the trustworthiness test of research data , and they can notdetermine research type using data analysis.Keywords: assessment, skills, qualitative research, guidance and counseling students